ANALISIS GESER BALOK-T BETON BERTULANG BERLUBANG MEMANJANG DENGAN MENGGUNAKAN METODE ELEMEN HINGGA NONLINIER - Kasmat Saleh Nur (Universitas Negeri Yogyakarta, 2010)
ABSTRACTThe presence of flanges on the reinforced concrete T-beam increases the shearcapacity, but if the beam-T is made in hollow elongated affect shear capacity. Thisresearch conducted to find numerical modelling of nonlinear finite element for hollowreinforced concrete. using the program ATENA V.2.1.10 which were then verified withnumerical experiment model. The results showed that the hole in hollow reinforcedconcrete is not enough affect the shear capacity but may reduce the ductility, in whichthe ductility decreases as the ratio of the hole increases.Keywords : Reinforcement concrete, Hollow core beam, Shear, Ductility, Crack pattern.